Avaliação do microbioma do queijo de coalho - Lima, Joelma Martins Pereira de (2017)
The coalho cheese is considered a cultural patrimony and has great social and economic importance for the northeastern Brazilian region. The evaluation of the microbiological conditions of this product becomes fundamental for the affirmation of food safety and investigation of the real characteristics that make this kind of cheese so peculiar. The objective of the study was to identify the microbial community of coalho cheese. Metagenomic target DNA was extracted from eight samples of coalho cheese, four of which were made from pasteurized milk and four from raw milk. The DNA of the samples was sequenced by the next generation sequencing technology using the 16S and 18S rDNA gene as the basis for the identification of the organisms. Sequencing analyzes revealed several prokaryotic pathogenic microorganisms such as Rothia dentocariosa, Elizabethkingia meningoseptica and Bacillus cereus, as well as bacterial genera belonging to the microbiota previously described as Lactobacillus, Lactococcus, Escherichia, Enterococcus. Several fungi, such as Candida tropicalis, Candida parapsilolis, Pichia membranifaciens, Tritirachium oryzae, Malassezia furfur and Kluyveromyces marxianus were identified in the eukaryotic research, as well as microorganisms that had not yet been described in rennet cheeses such as Vibrio rumoienses, Ruminococcus flavefaciens, Piscicoccus intestinalis and Dekkera bruxellensis